2020
DOI: 10.1021/acs.jpcc.0c07198
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Luminescent Supramolecular Hydrogel Based on the AIE Strategy of Gold Nanoclusters and their Application as a Luminescence Switch

Abstract: Gold nanoclusters (AuNCs) have been recognized as an emerging category of inorganic−organic hybrid luminescent materials owing to their ultrasmall size, good biocompatibility, and especially the aggregationinduced emission (AIE) property. Some works have been reported about the AIE property of AuNCs; however, the mechanism is still indistinct. In the present work, we studied the coassembly behavior of thiobarbituric acidmodified AuNCs (TBA-AuNCs) with Zn 2+ . The coassembly system could not only enhance the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Very recently, it was observed that the emission behavior of gold nanoclusters enhances drastically when metal ions (Zn 2+ , Cd 2+ ) are incorporated in the coassembly along with the morphological transformation. The enhanced emission was attributed to aggregation-induced emission (AIE) behavior of nanoclusters along with π–π stacking of ligands and ligand-to-metal charge transition (LMCT). Fan and co-workers previously showed an enhanced emission intensity of dipeptide self-assembly upon coordination with Zn 2+ and it was observed that metal ions with higher nuclear charge and polarizability induce more enhancement in the emission signal .…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, it was observed that the emission behavior of gold nanoclusters enhances drastically when metal ions (Zn 2+ , Cd 2+ ) are incorporated in the coassembly along with the morphological transformation. The enhanced emission was attributed to aggregation-induced emission (AIE) behavior of nanoclusters along with π–π stacking of ligands and ligand-to-metal charge transition (LMCT). Fan and co-workers previously showed an enhanced emission intensity of dipeptide self-assembly upon coordination with Zn 2+ and it was observed that metal ions with higher nuclear charge and polarizability induce more enhancement in the emission signal .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the aggregation-induced emission (AIE) strategy was found to significantly improve the emission intensity and quantum yield of metal NCs. The AIE of the metal NCs might be explained by the fact that the aggregation limits the vibration and rotation of the surface ligand molecules, which restrains the ligand-related nonradiative excited state relaxation and realizes the ligand-to-metal charge transfer (LMCT) and/or ligand-to-metal–metal charge transfer (LMMCT) triplet transition. ,, However, since metal NCs are extremely small in size, large surfaces might generate irregularities in the aggregates, making it difficult to form regular structures. , To solve this problem, self-assembly is considered as an effective strategy to achieve AIE, which can regulate the spatial distribution of metal NCs to form regular structures, thereby manipulating their luminescence properties. Zhang et al significantly enhanced the luminous intensity of Cu NCs through self-assembly strategies .…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, a balance of the H-bonding and electrostatic interactions governs the formation of assembly of ionic MNCs. For example, the self-assembly of thiobarbituric acid (TBA) protected Au NCs (Au NCs@TBA) has been driven by the Zn 2+ ions . TBA ligand consisting of H-bonding donor–acceptor sites, π–π stacking, and metal coordination sites first enable the formation of 1D nanofiber-like structure through H-bonding interaction, which upon addition of Zn 2+ ions gradually transformed into highly luminescent 3D bowknot-like aggregated gel structures because of the π–π stacking of the TBA ligands and strong electrostatic attraction between carboxylate groups of the TBA ligands and Zn 2+ ions.…”
mentioning
confidence: 99%
“…For example, the self-assembly of thiobarbituric acid (TBA) protected Au NCs (Au NCs@TBA) has been driven by the Zn 2+ ions. 79 TBA ligand consisting of H-bonding donor−acceptor sites, π−π stacking, and metal coordination sites first enable the formation of 1D nanofiber-like structure through H-bonding interaction, which upon addition of Zn 2+ ions gradually transformed into highly luminescent 3D bowknot-like aggregated gel structures because of the π−π stacking of the TBA ligands and strong electrostatic attraction between carboxylate groups of the TBA ligands and Zn 2+ ions. Similar to the MNC-impregnated nanogel, the solid-like hydrogel structure of Au NCs@TBA also improves their PL further, suggesting the AIE characteristics of Au NCs@TBA and the role of H-bonding together with many other interactions for the enhancement of AIE through gelation.…”
mentioning
confidence: 99%